Democracy and bureaucracy - Gruber, Judith E. (1997)
The issue in bureaucracy and democracy is one of control. This paper calls for greater control resources for elected officials whereby they can overcome the abundant power resources of bureaucrats. A process of exchange as against a process of authority is suggested as a strategic means of democratic control over bureaucracy. Successfully meeting the challenge of reconciling deeply cherished norms of popular control with dependence on appointed administrators requires acknowledgement not only of the rights of the controllers but also of the powers of the controlled. It requires thinking strategically about creating and marshaling alternative resources to counteract the abundant resources bureaucrats have, to circumvent control for both selfish and public spirited reasons. Such a focus on resources suggests the fruitfulness of conceptualizing democratic control more as a process of exchange than as an exercise of authority. - Reproduced
Keywords: Democracy - United States; Bureaucracy - United States; Bureaucracy